Modelagem mecanístico-empírica da interface revestimento asfáltico-base granular - Silva, Samuel de Almeida Torquato e (2017)
Prime coat is the bituminous binder application over the first subjacent granular layer underneath the asphalt surface course within a pavement structure. Beyond its functional roles, the prime coat is also responsible for the bonding between the asphaltic and the base layers, composing an asphalt coat-granular base interface. Although the importance of a strenght and stiff interface on pavement performance is well established in the literature, the bonding condition between the asphaltic and the base layers are oftentimes considered as i) perfectly bonded or ii) unbonded, despite the fact that it is known that these approaches are not coherent with the real interface mechanical behavior. To better understand this phenomenon and estimate stiffness and strength values for prime coat interface, it is proposed a mechanical model to describes and an experimental to assess interface mechanical parameters to be used in structural analysis. Prime coat interface is considered herein as a perfect elastoplastic material, which is also stress dependent and ruled by Mohr-Coulomb failure criteria. The results obtained suggest that the model and the proposed test are effective in represent and characterize the interface mechanical behavior. Model parameters were assessed from the test performed and used as input in a Finite Element Method analysis, by using interface finite elements developed in this research. The analysis results have shown that the interface studied in this research do not fail if only vertical field loads are considered. For this same situation and for the materials tested, interface parameters consideration was equivalent to consider the layers completely unbounded, suggesting that this specific interface performs an irrelevant structural role. Finally, the procedure proposed successfully answered the questions related to layer bonding conditions provided by the interface in asphaltic pavements. Nevertheless, it is necessary to perform more tests in order to guarantee more reliability to the conclusions obtained.